Efektivitas Penggunaan Media Video Animasi Terhadap Kecerdasan Linguistik Siswa Kelas II SD - Ulya, Ikfina Amaliya; Mubarok, Husni; Wiranti, Dwiana Asih (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
It's critical to understand the language intelligence of pupils in elementary school, especially within the lower grades, especially the ability to read, write and tell stories. Researchers will take advantage of current technological developments as an effort to minimize this. The technology that researchers use is through utilizing media in the manner of animated videos. This research seeks to evaluate how well animated video content works on the linguistic intelligence of class II students at SD Negeri 2 Bawu.Quantitative research is employed in this investigation. The approach taken in this study uses thePretest posttest methodology for one group in a Pre-Experimental Design. Techniques for analyzing data include normalcy, validity, and reliability tests, and homogeneity tests and T-Test using SPSS. The subjects in this study there were 23 class II students. The study's findings suggest that animated video content can improve linguistic intelligence in class II students at SD Negeri 2 Bawu by obtaining T-test data, namely tcount>ttable 3,192>1.714 using a significant value that of 0.04 this implies that there are differences and improvements by using animated video media on the linguistic aptitude of SD Negeri 2 Bawu’s class II pupils.